Preservation of Traditional Art in the Modern Era: A Case Study of Seudati Dance in the Disruption Era in Pidie Jaya Regency - Mujiburrahman, Mujiburrahman; Meliza, Richa; Riski, Aflia; Yunanda, Rizki; Kamil, Ade Ihsan; Chalid, Ibrahim; Rahmatika, Assyfa; Nizar, Raudatun (Andalas International Journal of Socio-Humanities, 2024)
The focus of this research is on the strategies for preserving Seudati dance by the Pidie Jaya government in the era of disruption. Pidie Jaya is one of the regencies known for the Seudati dance, and many prominent Seudati leaders, known as "syeh," hail from this region. This research was conducted in Pidie Jaya Regency, with the location chosen due to the observed phenomenon that the youth are no longer interested in learning and performing Seudati. Data collection techniques in this research included participant observation, where the researcher directly observed the subjects to gather data. In addition to participant observation, in-depth interviews were also employed as a technique for collecting data. The results of the research indicate that the youth are abandoning Seudati because the digital world is more appealing than Seudati. Furthermore, learning Seudati is not as easy as learning other dances. In response to these challenges, the Pidie Jaya government has made efforts to preserve Seudati through several approaches. First, they utilize digital media itself as a platform for Seudati campaigns. They also give recognition to Seudati maestros, creating a positive impression for all parties involved. The government promotes Seudati in extracurricular activities through the Gerakan Seniman Masuk Sekolah. Additionally, they are reactivating village dance studios and providing spaces for expression, such as the Pekan Kebudayaan Pidie Jaya.